2011
DOI: 10.1007/82_2011_152
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Functions of ADAR in Drosophila

Abstract: Drosophila melanogaster has a single Adar gene encoding a protein related to mammalian ADAR2 that edits transcripts encoding glutamate receptor subunits. We describe the structure of the Drosophila Adar locus and use ModENCODE information to supplement published data on Adar gene transcription, and splicing. We discuss the roles of ADAR in Drosophila in terms of the two main types of RNA molecules edited and roles of ADARs as RNA-binding proteins. Site-specific RNA editing events in transcripts encoding ion ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Studies with transgenic mouse embryos that are deficient in both ADAR and ADARB1 activity revealed that deficiency of ADARB1 leads to accumulation of specific miRNAs and corresponding targets, thereby suggesting an important role for ADARs in miRNA biogenesis (Luciano et al, 2004; Yang et al, 2006; Ohman, 2007; Heale et al, 2009; Alon et al, 2012; Vesely et al, 2012). Furthermore ADARs binding alone can affect miRNA biogenesis and function and RNA interference in the nervous system (Heale et al, 2009; Paro et al, 2012). The biological roles of ADAR3 are particularly interesting due to its broad substrate specificity (binding single-stranded as well as double-stranded RNA) and localization that is restricted to brain regions and post-mitotic neurons (Melcher et al, 1996; Chen et al, 2000).…”
Section: Dysregulated A–i Editing In Neurodegenerationmentioning
confidence: 99%
“…Studies with transgenic mouse embryos that are deficient in both ADAR and ADARB1 activity revealed that deficiency of ADARB1 leads to accumulation of specific miRNAs and corresponding targets, thereby suggesting an important role for ADARs in miRNA biogenesis (Luciano et al, 2004; Yang et al, 2006; Ohman, 2007; Heale et al, 2009; Alon et al, 2012; Vesely et al, 2012). Furthermore ADARs binding alone can affect miRNA biogenesis and function and RNA interference in the nervous system (Heale et al, 2009; Paro et al, 2012). The biological roles of ADAR3 are particularly interesting due to its broad substrate specificity (binding single-stranded as well as double-stranded RNA) and localization that is restricted to brain regions and post-mitotic neurons (Melcher et al, 1996; Chen et al, 2000).…”
Section: Dysregulated A–i Editing In Neurodegenerationmentioning
confidence: 99%
“…The profound importance of ADARs for normal development and neurophysiology in the absence of virus infection is illustrated in mice and flies by the phenotypes observed following genetic disruption of Adar genes or overexpression of ADAR proteins as reviewed by Hartner and by Keegan and colleagues in other chapters in this volume (Hartner and Walkley 2011; Paro et al 2011). Genetic knockout of Adar1 in the mouse in a manner that disrupts expression of both p110 and p150 (Hartner et al 2004, 2009; Wang et al 2004; XuFeng et al 2009) or only p150 (Ward et al 2011) results in embryonic lethality between embryonic days 11.5 and 12.5.…”
Section: Adars and Their Effects On Virus-host Interactionsmentioning
confidence: 99%
“…Differential 3′-end formation arising by termination within intron 6 produces truncated transcripts lacking the deaminase domain [13]. Among the best-studied examples of nucleotide-specific deamination by ADARs are mRNAs encoding mammalian [reviewed in 14] and several different Drosophila brain ligand- or voltage-gated ion channel proteins [reviewed in 15]. In situ localization studies have shown that dADAR mRNAs are primarily located in the ventral nerve cord and brain of the developing embryo [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…In situ localization studies have shown that dADAR mRNAs are primarily located in the ventral nerve cord and brain of the developing embryo [12,16]. There is a growing body of evidence that ADARs also have various editing-independent functions, likely arising from their roles as RNA-binding proteins [reviewed in 15]. In contrast to what is known about catalytically active full-length dADAR s, virtually nothing is known about the functions or phylogenetic distribution of the truncated dADAR isoform.…”
Section: Introductionmentioning
confidence: 99%